Konsep Adab dan Ta'dib dalam Pendidikan Islam: Relevansinya Bagi Pendidikan Karakter di Era Digital - Barratun Naqiyah; Ayu Handayani (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
This study examines the concepts of adab and ta'dib in Islamic education and their relevance to character education development in the digital era. Adab and ta'dib are fundamental concepts in Islamic educational tradition developed by scholars such as al-Attas, al-Ghazali, and Ibn Khaldun. The digital era presents new challenges for character education, including moral degradation, technology dependence, and weakening spiritual values. This research employs library research method with descriptive-analytical qualitative approach. The findings indicate that the concept of adab encompasses the formation of external and internal behavior aligned with Islamic values, while ta'dib emphasizes comprehensive educational processes covering intellectual, spiritual, and moral aspects. Both concepts are highly relevant to addressing character education problems in the digital era through integration of spiritual values in learning, strengthening teacher exemplary behavior, and wise technology utilization. Implementation of adab and ta'dib concepts can serve as alternative solutions in building character of digital generation with noble morals, intellectual intelligence, and wisdom in utilizing technology.